Capital Market Development and Stock Price Behavior in Nepal - Timilsina, Yogendra (NRB Economic Review, 2001)
This paper mainly focuses in tracing out the historical events contributing to the development process of capital market in Nepal. Implications of macro-economic fundamentals such as monetary policy, fiscal policy, major financial and economic incidents and/or announcements affecting the market prices of shares are examined in brief. The objective of the study is to find out the fair market prices of equities and test whether the present behaviour of equity prices will remain stable. Coefficients of correlation between the Earning per share and corresponding Market price on the one hand and Dividend per share and corresponding Market price on the other are also computed to know which one EPS or DPS has a higher degree of relationship with the market price. Further, in order to test the degree of explanatory power of the two in influencing the market price of share, Regression Equations of Market Price (Y) on EPS as well as on DPS are drawn. Regression results are statistically tested to derive the conclusion.